Mycobacterium Tuberculosis Detection in Pulmonary Specimens from Prospective Immigrants; Laboratory Data from Pakistan - Shafquat, Yusra; Jabeen, Kausar; Irfan, Muhammad; Wahab, Khalid; Hasan, Rumina (Infectious Diseases Journal of Pakistan, 2022)
Introduction: Pakistan is a high tuberculosis (TB) burden country. As such, pre-immigration TB screening for Pakistani travelers is required by several countries. Positivity rate amongst this group has not been reported previously. Objectives: To assess the culture positivity rate of Mycobacterium tuberculosis (MTB) in pulmonary specimens received from prospective immigrants in Pakistan. Method: Data for MTB culture requested during 2008-2016 from prospective immigrants were retrieved from laboratory database. TB culture request was based on physician’s discretion. Identification and cultivation of MTB was performed at AKU laboratory using standard methods. Results: A total of 172 cases, for which TB smear and culture was requested were included. MTB culture was positive in 13/172 (7.5%) cases of which 5 were smear positive and 8 smear negative. One case was smear positive and culture negative. Three additional cases were positive for non tuberculous mycobacteria (NTM). Conclusion: Our data shows a high culture positivity rate in prospective immigrants screened for TB. Use of rapid diagnostic tests such as Xpert MTB/Rif in immigrants’ pre and post migration from high TB incidence areas may lead to an early diagnosis and treatment.